A Stochastic Model of Epigenetic Dynamics in Somatic Cell Reprogramming - Floettmann, Max; Scharp, Till; Klipp, Edda (Frontiers in Physiology, 2012)
Somatic cell reprogramming has dramatically changed stem cell research in recent years. The high pace of new findings in the field and an ever increasing amount of data from new high throughput techniques make it challenging to isolate core principles of the process. In order to analyze such mechanisms, we developed an abstract mechanistic model of a subset of the known regulatory processes during cell differentiation and production of induced pluripotent stem cells. This probabilistic Boolean network describes the interplay between gene expression, chromatin modifications and DNA methylation. The model incorporates recent findings in epigenetics and reproduces experimentally observed reprogramming efficiencies and changes in methylation and chromatin remodeling. It enables us to investigate in detail, how the temporal progression of the process is regulated. It also explicitly includes the transduction of factors using viral vectors and their silencing in reprogrammed cells, since this is still a standard procedure in somatic cell reprogramming. Based on the model we calculate an epigenetic landscape. Simulation results show good reproduction of experimental observations during reprogramming, despite the simple stucture of the model. An extensive analysis and introduced variations hint towards possible optimizations of the process, that could push the technique closer to clinical applications. Faster changes in DNA methylation increase the speed of reprogramming at the expense of efficiency, while accelerated chromatin modifications moderately improve efficiency.